DEVELOPING INSTRUCTIONAL MATERIAL FOR BIOLOGY EDUCATION DEPARTMENT STUDENTS OF IAIN RADEN INTAN LAMPUNG - Hidayat, Agus (Universitas Islam Negeri Raden Intan Lampung, 2013)
The purpose of this study is to provide the students and the lecturers with an appropriate instructional material that is in-line with the syllabus and fit the students’ needs. The research was conducted using the procedures of research and development (R&D) that consist of need assessment, planning, material development, evaluation and revision, field testing, and the last is final productrevision. The data were collected through interview, questionnaire, observation, field notes, and expert validation. The result of the research is that the product of the research is developed into ten units. Each unit was developed to contain three main sections, namely, reading section, grammar section, and speaking section. The instructional material also contains various exercises both written and spoken so that the students could be actively involved in the teaching and learning activities. The media included in the instructional material was selected to help the students in learning by providing media in multimedia format in theform of videos, songs, and dialogues and monologues. Students also could access websites that are suggested in the instructional material that contain online English games and additional materials.